Communications - Towards Family-Friendly Intensive Care - Abdul Karim, Othman; Mohd Faeiz, Pauzi; Siti Norazlina, Juhari; Mohd Nazri, Ali (2017)
Communications play a major role in management and caring of patients in the intensive care unit. It’s also contribute to a major percentage of complaints received by staffs in every intensive care unit from family members¹. To move towards family-friendly intensive care by improving communications between patient’s family members and staffs in intensive care unit